Towards lignin valorisation: comparing homogeneous catalysts for the aerobic oxidation and depolymerisation of organosolv lignin1. Issue 86 (18th September 2015) - Díaz-Urrutia, Christian; Chen, Wei-Ching; Crites, Charles-Oneil; Daccache, Jennifer; Korobkov, Ilia; Baker, R. Tom
<x xml:space="preserve">Abstract</x> Lignin is a unique potential source of aromatic chemicals derived from renewable resources.